Anatomical parameters of Pisum sativum seedlings under the influence of macro- and nanoparticles of zinc - Cерікбай А.Т.; Агеев, Д.В.; Айткулов, А.М. (Fundamental and Experimental Biology, 2023)
In Kazakhstan, the physicochemical properties of the nanoparticle were studied, but the physiological properties and toxicity to living organisms were not studied earlier. These studies have not been conducted in Kazakhstan, which presents broad prospects for scientific research. This paper presents the results of a comparative study of the anatomy of Pisum sativum seedlings exposed to macro- and nanoparticles of zinc of various concentrations (5, 10, 20 and 200 mg/100 ml). The anatomy of cross sections of vegetative organs of pea seedlings was studied. It has been established that zinc macro- and nanoparticles cause changes in the diameter of conductive beams, the thickness of internal and external tissues of the stem and root of seedlings. Differences in the influence of zinc nanoparticles on plant life processes depending on their concentration and the manifestation of their toxicity have been established. Thus, the determination of ways and means of the impact of metal nanoparticles on a living organism is an extremely important and relevant work necessary to establish scientifically-based concentrations and sizes of nanoparticles in water, air or in the composition of various materials with which a person comes into contact.